Risk Assessment of Productivity Recovery Post Occupational Accident in Indonesia - Anityasari, Maria; Bangsawan, Gung Made Arya; Wessiani, Naning Aranti (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Indonesia's public health provider, the Insurance Administration Organization (IAO), provides universal coverage for Work Accident Insurance. As an initiative, it has failed to support all workers. This study assesses productivity recovery risks and associated future costs following occupational accidents, employing risk management methods and scenario analyses to aid decision-making in Indonesia. Focusing on formal workers in Surabaya, this research examines the balance between government benefits and expected productivity rebound upon return. Six risk types are identified and analysed, while the most prevalent risks involve workers still undergoing treatment with uncertain outcomes. As existing coverage schemes risk negative cash flow and deficits, this study also calculates the budget needed for zero-accident targets and maximum compensation to balance government obligations and workers' remuneration. This study has successfully captured the critical factors that can lead to refining coverage and addressing financial shortfalls, allowing improved support for workers' recovery and return productivity.